Differential Toxicity of Agricultural Fungicides Toward Three Cyanobacterial and Five Green Algal Species - Jianyi, Ma; Senmiao, Tong; Pinwei, Wang; Jianmeng, Chen (Asian Journal of Chemistry, 2010)
Six fungicides were tested to examine toxicity to cyanobacteria and green-algae. The results indicated that: (1) the decreasing order of the toxicity was: chlorothalonil > hexaconazole > cymoxanil > benalaxyl > fosetyl-aluminum > metalaxyl; (2) the sensitivity of various species of algae exposed to benalaxyl, cymoxanil and hexaconazole varied by one order of magnitude and those exposed to metalaxyl and chlorothalonil varied by two orders of magnitude; (3) cyanobacteria were less sensitive to metalaxyl, chlorothalonil, cymoxanil and fosetylaluminum than were green algae. The decreasing order of ecosystem risk was fosetyl-aluminum > chlorothalonil > metalaxyl > cymoxanil > hexaconazole > benalaxyl.